31. RESULTS OF THE ANTIBIOTICS TREATMENT COMBINED WITH LIVER ABSCESS DRAINAGE AT NGUYEN TRI PHUONG HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Background: Percutaneous drainage of liver abscess is the initial treatment of choice for abscesses more significant than 5 cm in size and has long been applied in many hospitals in Vietnam. Object: Evaluation of the effectiveness of antibiotic treatment of liver abscess with drainage under ultrasound guidance. Subjects and methods: Retrospective study of patients with a liver abscess who were treated with antibiotics and drained the abscess under ultrasound guidance at Nguyen Tri Phuong Hospital from January 2017 to March 12/2022. Results: There were 61 patients included in the study. The male/female ratio of 1.65/ first; an average 56.1 ± 12.3 years old, history of diabetes accounted for 32.8%; The prominent clinical symptoms are fever (88.5%), and right upper quadrant pain (85.2%). The liver abscess located in the right liver accounted for 73.4%, most of which was a single abscess (78.7%). First-line antibiotic treatment is Cephalosporin III generation combined with intravenous metronidazole. Most are sensitive to third-generation Cephalosporins (49.2%), 8.2% are multi-resistant ESBL-secreting bacteria using Carbapenems. The treatment success rate is high (96.7%). Conclusion: Treatment of liver abscess with antibiotics combined with ultrasound-guided drainage is an effective and safe measure. Most cases are only intervention one time with a high success rate.
Keywords: Liver abscess, antibiotics, ultrasound-guided drainage.